HeLa cell beta-tubulin gene transcription is stimulated by adenovirus 5 in parallel with viral early genes by an E1a-dependent mechanism. - Stein, R (1984)
We report that the rate of transcription of cellular beta-tubulin genes increases during the early phase of adenovirus infection of HeLa cells, with kinetics very similar to those routinely found for viral genes. This activation depends upon adenovirus early region E1a, which encodes products that activate early virus transcription. To compare the responses of viral and cellular genes to E1a, we infected HeLa cells with dl312, a transcriptionally inactive deletion mutant that lacks a functional E1a gene. We then superinfected the cells with a helper virus, dl327, which encodes active E1a products, and measured changes in the rates of transcription of various cell and viral genes. Early region E3 of dl312 was activated 0 to 6 h postinfection and then repressed at 8 h postinfection, thus reproducing the two-step kinetics characteristic of a wild-type infection. Synthesis of beta-tubulin nuclear RNA was also transiently induced two- to six-fold, rising and falling in a manner similar to E3 transcription. An increase in helper virus multiplicity gave an increase in beta-tubulin stimulation, but dl312 alone, even at a high multiplicity of infection, gave no induction, confirming the requirement for E1a. beta-Actin nuclear RNA was actively synthesized before infection, but it was not further stimulated by the virus. Cellular beta-globin gene transcription was not stimulated by the virus, although transcription of a transfected beta-globin plasmid was induced by the virus or from a cotransfected E1a expression plasmid. We conclude that adenovirus 5 can stimulate beta-tubulin gene transcription. We discuss the significance for the viral life cycle of viral stimulation of cell genes and consider possible mechanisms in the light of the results obtained with beta-actin and beta-tubulin.